2019
DOI: 10.1080/15548627.2019.1615302
|View full text |Cite
|
Sign up to set email alerts
|

Axonal autophagosome maturation defect through failure of ATG9A sorting underpins pathology in AP-4 deficiency syndrome

Abstract: Adaptor protein (AP) complexes mediate key sorting decisions in the cell through selective incorporation of transmembrane proteins into vesicles. Little is known of the roles of AP-4, despite its loss of function leading to a severe early onset neurological disorder, AP-4 deficiency syndrome. Here we demonstrate an AP-4 epsilon subunit knockout mouse model that recapitulates characteristic neuroanatomical phenotypes of AP-4 deficiency patients. We show that ATG9A, critical for autophagosome biogenesis, is an A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(102 citation statements)
references
References 82 publications
7
95
0
Order By: Relevance
“…We next examined spinal motor axons and found that morphants exhibited shorter axonal length, indicating that SPG52 may be important for the outgrowth of motor axons. This is consistent with impaired neuron outgrowth found in cultured neurons from Ap4e1 knockout mice 16,17 and similar to results seen in several zebrafish models of HSP including spastin, 18 atl1 , 19 and spatacsin 20 . Seizures are found in about two‐thirds of AP‐4‐HSP patients and febrile seizures are common early in life 3 .…”
Section: Discussionsupporting
confidence: 85%
“…We next examined spinal motor axons and found that morphants exhibited shorter axonal length, indicating that SPG52 may be important for the outgrowth of motor axons. This is consistent with impaired neuron outgrowth found in cultured neurons from Ap4e1 knockout mice 16,17 and similar to results seen in several zebrafish models of HSP including spastin, 18 atl1 , 19 and spatacsin 20 . Seizures are found in about two‐thirds of AP‐4‐HSP patients and febrile seizures are common early in life 3 .…”
Section: Discussionsupporting
confidence: 85%
“…The ubiquitin ligase TRIM32 stimulates ULK1 activity via unanchored K63-linked polyubiquitin to regulate muscle autophagy in response to atrophic stimuli [66][67][68]. Autophagy includes the following four stages: autophagy initiation, autophagosome formation, autophagosome-lysosome fusion, and the degradation of autophagic substrates [69]. It has been shown that tumor of the central nervous system with the BRAFV600E mutation are autophagy-dependent, and late stage inhibition of autophagy improves the response to targeted BRAF inhibitors (BRAFi) in sensitive and resistant cells [70].…”
Section: The Canonical Role Of Ulk1mentioning
confidence: 99%
“…In the absence of AP-4, ATG9A accumulates at the TGN of diverse cell types, including neuronal and nonneuronal cells (Behne et al, 2020;Davies et al, 2018;De Pace et al, 2018;Ivankovic et al, 2020;Mattera et Davies et al, 2020. To assess whether DAGLB exhibits a similar missorting phenotype in AP-4-deficient cells, we used immunofluorescence microscopy.…”
Section: Daglb Accumulates At the Tgn Of Ap-4 Deficient Hela And Neurmentioning
confidence: 99%
“…Accordingly, mutations in the axonal transport machinery are implicated in a broad range of neurodevelopmental and neurodegenerative diseases (reviewed in Guedes-Dias & Holzbaur, 2019). We and others recently discovered that adaptor protein complex 4 (AP-4) is required for the axonal delivery of vesicles containing the autophagy protein ATG9A (Davies et al, 2018;De Pace et al, 2018;Ivankovic et al, 2020;Mattera et al, 2017). Biallelic loss-of-function mutations in any of the four subunits of AP-4 (AP4B1, AP4E1, AP4M1, AP4S1) cause AP-4 deficiency syndrome, characterised by global developmental delay, intellectual disability, seizures and progressive spasticity, with onset of symptoms in early infancy (Abou Jamra et al, 2011;Moreno-De-Luca et al, 2011;Verkerk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation